THEORETICAL REVIEW OF THE ECONOMICS OF PAPER MACHINE OPERATION (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper reviews the variables affecting the production capacity of a paper machine. Paper grammage,machine deckle and operating speed of the machine are cited as major determinants, amongst others, in theevaluation of the machine production capacity. The daily production capacity of a paper machine in finishedmetric tonnage (FMT) can be calculated, using the formula P = 0.00006dvgc1c2c3 (tons/day). Variation ofthe production variables upward can translate to increase in machine output, though increments in thesevariables need to be carried out in a manner not to compromise product quality for a given paper grade.Optimum profitability of paper machine operation is enhanced by the production of mid-range grammagesof paper. While production loss can be reduced by promptly identifying and defining the various categoriesof faults affecting machine runnability, upholding scheduled maintenance plan for the machine system andensuring sustained capacity building for technical staff in paper machine operation are prerequisites forimproved paper machine efficiency. Globally, loss time analysis is used by mills to assess ways of reducingproduction loss and as a tool to assess the economics of paper machine operation, with a view to evaluatingthe efficiency or otherwise of the operating, maintenance and service departments in machine roomoperation.